2008
DOI: 10.1111/j.1365-2699.2008.02001.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic structure of Pinus strobiformis Engelm. across the Chihuahuan Desert filter‐barrier

Abstract: Aim To explore the genetic and phylogeographic structure of a temperate forest species, Pinus strobiformis Englem., in a subtropical region in the context of climate change during the Pleistocene. It is expected that the colder conditions during glacial stages favoured range expansions of P. strobiformis, thus promoting gene flow.Location Mexico and the United States.Methods Estimates of genetic diversity and structure were obtained using chloroplast microsatellite loci of 23 populations of P. strobiformis acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 54 publications
7
43
3
1
Order By: Relevance
“…Since P. ayacahuite is geographically close to P. strobiformis, and there is evidence of introgression (Perez de la Rosa 1993; Ortíz-Medrano et al 2008; Moreno-Letelier and Piñero 2009), we expected a higher genetic similarity at all nuclear loci. However, what we observe is that only housekeeping genes show a pattern of high differentiation similar to cytoplasmic markers between these two species (Moreno-Letelier and Piñero 2009;Moreno-Letelier et al 2013), but candidate loci show lower differentiation. High differentiation in housekeeping genes could be the result of an older divergence between these two species.…”
Section: Genetic Structure and Isolation Testsmentioning
confidence: 62%
See 3 more Smart Citations
“…Since P. ayacahuite is geographically close to P. strobiformis, and there is evidence of introgression (Perez de la Rosa 1993; Ortíz-Medrano et al 2008; Moreno-Letelier and Piñero 2009), we expected a higher genetic similarity at all nuclear loci. However, what we observe is that only housekeeping genes show a pattern of high differentiation similar to cytoplasmic markers between these two species (Moreno-Letelier and Piñero 2009;Moreno-Letelier et al 2013), but candidate loci show lower differentiation. High differentiation in housekeeping genes could be the result of an older divergence between these two species.…”
Section: Genetic Structure and Isolation Testsmentioning
confidence: 62%
“…Our results clearly support IBE of P. flexilis, as it is both ecologically (MorenoLetelier et al 2013), and genetically differentiated from its sister species at candidate loci. However, in addition to the pattern of IBE in candidate genes, genetic differentiation of housekeeping genes and cytoplasmic markers between P. ayacahuite and P. strobiformis suggests that isolation by distance, genetic drift and secondary contact could have also played a role the observed genetic patterns of these two species (Moreno-Letelier and Piñero 2009;Strasburg et al 2012;Abbott et al 2013). In either case, these combined factors could help explain the recent diversification of pines in North America (Gernandt et al 2008), which has resulted in high ecological and morphological diversity, despite widespread shared polymorphism (Syring et al 2007a, b;Moreno-Letelier and Piñero 2009;Willyard et al 2009;Jardón-Barbolla et al 2011).…”
Section: Genetic Structure and Isolation Testsmentioning
confidence: 92%
See 2 more Smart Citations
“…Published molecular studies based on isozymes and DNA markers (low-copy unlinked nuclear loci and RAPDs) revealed low genetic diversity in this species (Castillo et al, 2009). Molecular marker-based studies in the P. strobiformis-P. ayacahuite complex have been limited to genetic diversity assessment using isozymes (Hernández-Gónzalez 1990;Ledig, 1998), RAPDs (Castro-Félix et al, 2006, and chloroplast microsatellite markers (Ortíz-Medrano et al, 2008;Moreno-Letelier and Piñero, 2009).…”
Section: Introductionmentioning
confidence: 99%